German Economy Winter 2019 - German economy overcomes slowdown only gradually - Jens Boysen-Hogrefe; Salomon Fiedler; Dominik Groll; Nils Jannsen; Stefan Kooths; Saskia Mösle; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW), 2019)
The German economy is recovering only gradually. After a weak summer half-year, gross domestic product will hardly do more than stagnate in the final quarter of the current year. Economic activity still provides two contrasting pictures. The main reason for the ongoing downturn, which began last year, is the significant decline in industrial production. This was mainly due to the gloomy global economic environment, since reduced investment worldwide due to the high level of global economic uncertainty had a particularly negative impact on the German economy, which is specialized in the production of capital goods. In the meantime, the investment climate in Germany has also deteriorated noticeably. As a result, companies are likely to significantly reduce their investment activity in the coming quarters. The weak industrial economy is also increasingly affecting the industry-related services companies. In contrast, the consumer-related service sectors continue to expand. Despite the fact that employment growth has now slowed considerably, disposable incomes of private households continue to rise significantly. In addition to wage increases which continue to be quite strong, numerous income-increasing fiscal policy measures are also contributing to this. The construction industry is still booming, not least due to the continuing favorable financing conditions. Over the course of the coming year, overall economic production should gradually pick up again somewhat. This is supported by the slight recovery in the global economy. As a result, industrial production should find its bottom and at least pick up again somewhat. At 1.1 percent, GDP growth in 2020 is likely to be much higher than in the current year, where an increase by 0.5 percent is expected. However, the higher growth rate in the coming year is primarily due to the higher number of working days. Against this backdrop, the surpluses of public budgets will decline significantly: While spending will continue to expand strongly, revenues will be noticeably burdened by the weak economy. After the record surplus of over 60 billion euros in 2018, we expect a slight deficit in 2021. – – Die Konjunktur in Deutschland fasst nur allmählich wieder Tritt. Nach einem schwachen Sommerhalbjahr dürfte das Bruttoinlandsprodukt auch im Abschlussquartal des laufenden Jahres kaum mehr als stagnieren. Die wirtschaftliche Entwicklung bleibt dabei zweigeteilt. Maßgeblich für den anhaltenden Abschwung, der bereits im vergangenen Jahr einsetzte, ist die deutlich rückläufige Industrieproduktion; mittlerweile befindet sich die Industrie sogar in der Rezession. Dazu beigetragen hat vor allem das eingetrübte weltwirtschaftliche Umfeld, wobei die hohe weltweite wirtschaftspolitische Unsicherheit die auf die Produktion von Investitionsgütern spezialisierte deutsche Wirtschaft in besonderem Maße belastet. Mittlerweile hat sich auch in Deutschland das Investitionsklima spürbar verschlechtert. In der Folge dürften die Unternehmen ihre Investitionstätigkeit in den kommenden Quartalen noch einmal deutlich zurückfahren. Die schwache Industriekonjunktur zieht auch die unternehmensnahen Dienstleistungsbranchen zunehmend in Mitleidenschaft. Demgegenüber befinden sich die konsumnahen Dienstleistungsbereiche weiter auf Expansionskurs. Trotz des nunmehr deutlich langsameren Beschäftigungsaufbaus ziehen die verfügbaren Einkommen der privaten Haushalte weiter deutlich an. Neben den weiter recht kräftigen Lohnzuwächsen tragen dazu auch zahlreiche einkommenserhöhende Maßnahmen seitens der Finanzpolitik bei. Die Baubranche boomt nach wie vor, nicht zuletzt aufgrund der weiterhin günstigen Finanzierungsbedingungen. Im Verlauf des kommenden Jahres dürfte sich die gesamtwirtschaftliche Produktion allmählich wieder etwas beleben. Dafür spricht auch die wieder leicht anziehende Weltkonjunktur. In der Folge dürfte die Industrieproduktion ihren Boden finden und zumindest wieder etwas anziehen. Eine große Dynamik wird die Konjunktur dabei freilich nicht entfalten. Zwar dürfte das Bruttoinlandsprodukt im Jahr 2020 mit 1,1 Prozent deutlich stärker zulegen als im laufenden Jahr, für das sich ein Anstieg von 0,5 Prozent abzeichnet. Für die höhere Zuwachsrate im kommenden Jahr ist jedoch vor allem die dann höhere Zahl an Werktagen verantwortlich. Die Budgetüberschüsse der öffentlichen Haushalte werden deutlich zurückgehen: Während die Ausgaben weiterhin kräftig ausgeweitet werden, werden die Einnahmen durch die schwache Konjunktur spürbar belastet. Nach dem Rekordüberschuss in Höhe von über 60 Mrd. Euro im Jahr 2018 rechnen wir für das Jahr 2021 mit einem leichten Defizit.
Keywords: 330; business cycle forecast; stabilization policy; leading indicators; outlook